2001
DOI: 10.4049/jimmunol.167.5.2772
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 and Aspirin-Triggered 15-Epi-Lipoxin A4 Antagonize TNF-α-Stimulated Neutrophil-Enterocyte Interactions In Vitro and Attenuate TNF-α-Induced Chemokine Release and Colonocyte Apoptosis in Human Intestinal Mucosa Ex Vivo

Abstract: Lipoxins (LXs) are lipoxygenase-derived eicosanoids and putative endogenous braking signals for inflammation in the gastrointestinal tract and other organs. Aspirin triggers the production of 15-epimers during cell-cell interaction in a cytokine-primed milieu, and aspirin-triggered 15-epi-5(S),6(R),15(S)-trihydroxy-7,9,13-trans-11-cis-eicosatetraenoic acid (15-epi-LXA4) may contribute to the bioactivity profile of this prototype nonsteroidal anti-inflammatory drug in vivo. We determined the effect of LXA4, 15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…These studies confirm the role of proinflammatory cytokines in immune cell adherence in salivary epithelium and provide the first evidence for direct antiinflammatory effects of LXA 4 in salivary epithelium. Previous studies in intestinal epithelial cell lines and colonic epithelium indicated that LXA 4 and its stable analogs downregulate chemokine secretion (38). LXA 4 also enhanced mucosal antimicrobial protection by stimulating the expression of the bactericidal/permeability-increasing protein (BPI) in oral and intestinal epithelial cells (14), and accelerated epithelial wound closure in murine cornea (40).…”
Section: Discussionmentioning
confidence: 99%
“…These studies confirm the role of proinflammatory cytokines in immune cell adherence in salivary epithelium and provide the first evidence for direct antiinflammatory effects of LXA 4 in salivary epithelium. Previous studies in intestinal epithelial cell lines and colonic epithelium indicated that LXA 4 and its stable analogs downregulate chemokine secretion (38). LXA 4 also enhanced mucosal antimicrobial protection by stimulating the expression of the bactericidal/permeability-increasing protein (BPI) in oral and intestinal epithelial cells (14), and accelerated epithelial wound closure in murine cornea (40).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that several recent studies have suggested that LXA 4 opposes the inflammatory property of TNF-␣ and IL-1␤. Indeed, LXA 4 inhibits IL-1␤-induced release of IL-6, IL-8, and matrix metalloproteinase-3 in fibroblast-like synoviocytes, antagonizes TNF-␣-initiated IL-1␤ production by neutrophils Sodin-Semrl et al, 2000) and attenuates TNF-␣-stimulated IL-8 and monocyte chemoattractant protein-1 release by colonic cell lines (Gronert et al, 1998;Goh et al, 2001). Moreover, LXA 4 stable analogs are able to inhibit the renal synthesis of IL-1␤ in experimental ischemic renal injury (Leonard et al, 2002;Kieran et al, 2003;Wu et al, 2005) and to block the extracellular signal-regulated kinase-dependent TNF-␣ secretion from human T cells (Ariel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Lipoxin-A 4 (or its analogs) reduces the degree of inflammation (Takano et al, 1997;Goh mice. ICAM-1 expression; sham-operated group (A), wild-type group subjected to renal I/R (B), zileuton treated group subjected to renal I/R (C), and 5-LOX Ϫ/Ϫ mice group subjected to renal I/R (D).…”
Section: -Lipoxygenase In Renal I/r Injury 223mentioning
confidence: 99%